2015
DOI: 10.3109/17453674.2015.1034608
|View full text |Cite
|
Sign up to set email alerts
|

Historical view and future demand for knee arthroplasty in Sweden

Abstract: Background and purpose The incidence of knee osteoarthritis will most likely increase. We analyzed historical trends in the incidence of knee arthroplasty in Sweden between 1975 and 2013, in order to be able to provide projections of future demand.Patients and methods We obtained information on all knee arthroplasties in Sweden in the period 1975–2013 from the Swedish Knee Arthroplasty Register, and used public domain data from Statistics Sweden on the evolution of and forecasts for the Swedish population. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 39 publications
4
65
1
2
Order By: Relevance
“…The incidence of knee arthroplasty in females was found to be greater than that in males in our study, but the results of previous studies have also shown that the proportion of female patients has decreased with time (Nemes et al. 2015). Moreover, the sex distribution may also vary between nations (Paxton et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of knee arthroplasty in females was found to be greater than that in males in our study, but the results of previous studies have also shown that the proportion of female patients has decreased with time (Nemes et al. 2015). Moreover, the sex distribution may also vary between nations (Paxton et al.…”
Section: Discussionmentioning
confidence: 99%
“…2011, Nemes et al. 2015). One study delivered projections for primary and revision hip and knee arthroplasty in the United States from 2005 to 2030 (Kurtz et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les taux de révision chirurgicale ont été plus élevés chez les patients hypertendus et ceux qui souffraient de G iven the aging population, the incidence and prevalence of osteoarthritis is expected to increase, and consequently the demand for total joint replacement (TJR) continues to rise. 1 In addition, more TJR procedures are being performed in older patients and those with multiple medical comorbidities. 2,3 Such patients are inevitably at a higher risk for serious postoperative complications and may require more rigorous optimization of their medical condition preoperatively and more in-depth discussion when obtaining informed consent.…”
Section: Contextementioning
confidence: 99%
“…For instance, in Sweden the estimated number of total knee arthroplasty (TKA) per 100.000 residents aged 40 years and older is 334 for the year 2020, while the projected incidence of TKA, in this community reaches 469 per 100.000 subjects in 2130 [1]. In the UK, the number of total hip arthroplasty (THA) and TKA procedures performed in 2035 is estimated to double compared to the numbers from 2010 [2].…”
Section: Introductionmentioning
confidence: 99%